1994
DOI: 10.2176/nmc.34.360
|View full text |Cite
|
Sign up to set email alerts
|

“Kissing Aneurysms” of the Internal Carotid Artery

Abstract: Five patients with kissing aneurysms (adherent internal carotid-posterior communicating artery and ipsilateral internal carotid-anterior choroidal artery aneurysms) are reported. There was female predominance and the subarachnoid hemorrhage was commonly due to rupture of the proximal posterior communicating artery aneurysm. Despite the demonstration of angiographic cleavage, the two aneurysms adhere to each other, which makes surgical dissection difficult. Meticulous dissection of the aneurysmal necks and pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 5 publications
0
26
0
Order By: Relevance
“…Eighteen cases of kissing aneurysms including the present case have been reported 2,3,[5][6][7][8][9] (Table 1). Four patients were males and 14 were females, aged from 26 to 59 years (mean 44.7 yrs) with SAH and 21 to 60 years (mean 46.3 yrs) without SAH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eighteen cases of kissing aneurysms including the present case have been reported 2,3,[5][6][7][8][9] (Table 1). Four patients were males and 14 were females, aged from 26 to 59 years (mean 44.7 yrs) with SAH and 21 to 60 years (mean 46.3 yrs) without SAH.…”
Section: Discussionmentioning
confidence: 99%
“…5,6) Furthermore, the working space around the neck is narrow, and the aneurysms are difficult to clip and easy to rupture because the kissing point is sometimes fibrous with adhesion (Table 1). In general, the interhemispheric approach is supposed to provide a wider working space.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6) Yasargil reported that KAs were observed in 2 (0.2%) of 1012 cases with cerebral aneurysms, 2) while in the report by Komiyama et al, it was mentioned that KAs were observed in 5 (0.9%) of 531 aneurysm patients, indicating the incidence thereof is rare. 7) Regarding the cause of KA, Jefferson et al reported that a family history of subarachnoid hemorrhage (SAH) was observed in two of five cases 1) ; however, Komiyama et al reported that no family history of SAH was observed in any of the five KA cases and the genetic predisposition of KAs is unknown. 7) In a review of 14 KA cases, it was reported that the onset of SAH was common, among which posterior communicating aneurysms along with anterior choroidal aneurysms were the most common, observed in nine cases.…”
Section: Case 2 (Fig 2)mentioning
confidence: 99%
“…7) Regarding the cause of KA, Jefferson et al reported that a family history of subarachnoid hemorrhage (SAH) was observed in two of five cases 1) ; however, Komiyama et al reported that no family history of SAH was observed in any of the five KA cases and the genetic predisposition of KAs is unknown. 7) In a review of 14 KA cases, it was reported that the onset of SAH was common, among which posterior communicating aneurysms along with anterior choroidal aneurysms were the most common, observed in nine cases. 8) Concerning treatment method and prognosis, as mentioned by Yasargil, 2) the surgical treatment of KA is difficult due to difficulty in procedures such as exfoliation and clipping operations during surgery, thereby making surgery treatment challenging, and in the review of 15 KA cases, it was reported that a complication in which the anterior choroidal artery became blocked was observed in 3 of the 15 cases (20%) that underwent surgery.…”
Section: Case 2 (Fig 2)mentioning
confidence: 99%